2019
DOI: 10.1002/poc.3965
|View full text |Cite
|
Sign up to set email alerts
|

The quest for a triplet ground‐state alkene: Highly twisted C═C double bonds

Abstract: Density functional theory and extrapolated CCSD(T) computations of several "anti-Bredt" alkenes were carried to explore possible 1,2-diyl "alkene" candidates with a triplet ground state. Ten candidates containing twisted double bonds at the bridgehead positions of bicyclic structures (1-6) or adamantene (7-10) derivatives were studied. Based on a combination of ring strain, rigid scaffolding, and steric crowding, four species were identified to have surprisingly low singlet-triplet energy gaps (lower than 4 kc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 66 publications
0
7
0
Order By: Relevance
“…[11][12][13][14][15][16][17] The performance of such molecular devices critically depends on electronic and steric features of the π system containing the switchable bond. All of these applications have created considerable interest in the properties of distorted π systems, ranging from simple alkenes [18,19] to complex polycyclic aromatics. [20][21][22][23] The equilibrium twist angle θ eq and the isomerization barrier of an alkene are interrelated and can be controlled by changes of the bond order and by steric effects.…”
Section: Introductionmentioning
confidence: 99%
“…[11][12][13][14][15][16][17] The performance of such molecular devices critically depends on electronic and steric features of the π system containing the switchable bond. All of these applications have created considerable interest in the properties of distorted π systems, ranging from simple alkenes [18,19] to complex polycyclic aromatics. [20][21][22][23] The equilibrium twist angle θ eq and the isomerization barrier of an alkene are interrelated and can be controlled by changes of the bond order and by steric effects.…”
Section: Introductionmentioning
confidence: 99%
“…Overcrowded ethylene, given a distorted C=C bonds by sterically bulky substituents, is a typical example of an external stimuli‐responsive molecule whose structural and physical properties can be significantly altered by releasing the strain energy upon stimulation [1–14] . Bianthrone 1 , one of the overcrowded ethylenes, has two conformational isomers, a major folded form and a minor twisted form, to avoid steric repulsion (Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…Overcrowded ethylene, given a distorted C=C bonds by sterically bulky substituents, is a typical example of an external stimuli-responsive molecule whose structural and physical properties can be significantly altered by releasing the strain energy upon stimulation. [1][2][3][4][5][6][7][8][9][10][11][12][13][14] Bianthrone 1, one of the overcrowded ethylenes, has two conformational isomers, a major folded form and a minor twisted form, to avoid steric repulsion (Figure 1). [1,2,14] Recently, we demonstrated that the energy gap between conformers can be minimized by introducing alkoxy groups at the 3,3',6,6'-positions and that a derivative with alkyl chains of eight carbon atoms gave twisted conformer crystals that had never been isolated before.…”
Section: Introductionmentioning
confidence: 99%
“…A trapped bicyclo[3.2.2]non-1ene dimer, formed by facile stepwise [2 + 2] cycloaddition of the bridgehead double bonds, was first reported by Wiseman et al 18 Dimers of adamantene form readily upon dehalogenation of 1,2-diiododamantane. 19,20 By comparing the reaction of 2norbornene (16) to that of bicyclo[4.2.1]non-1-ene (12) and bicyclo [3.3.1]non-1-ene ( 14), Becker and Hohermuth showed that the strained double bonds of 12 and 14 yielded faster stepwise [2 + 2] cycloadditions with 1,1-dichloro-2,2difluoroethene and at milder conditions. 21 12 and 14 also gave facile concerted [2 + 2] cycloaddition reactions with a ketene.…”
mentioning
confidence: 99%
“…Recently, Houk et al reported an example of an enzyme catalyzed thermal [2 + 2] cycloaddition reaction . In this computational study, we explore whether twisting a double bond , such as those in an anti-Bredt alkenemight facilitate stepwise [2 + 2] cycloaddition reactions.…”
mentioning
confidence: 99%